KAJIAN METODE MASERASI EKSTRAK DAUN TEH HIJAU (Camellia sinensis) DENGAN BERBAGAI PELARUT - Gunawan, Fikri Iqlilah; Aulia Putri, Silmi; Ulfa Ramdhanawati, Vania; Umami, Muhimatul (INSTITUT AGAMA ISLAM NEGERI AMBON, 2024)
Green tea is an ingredient that contains a lot of secondary metabolites in it. Flavonoids, polyphenols, terpenoids and saponins are types of secondary metabolites that have health benefits, namely antioxidant, anti-inflammatory and anticancer properties. One way to obtain these various compounds is by extraction using the maceration method, where the active compounds are dissolved using methanol, water, ethyl acetate or ethanol. This study aims to determine the type of solvent that is widely used in the maceration method for extracting green tea leaves. The data collection method used in preparing this journal review is literature study from various journals, books and research articles originating from Google Scholar. The results show that the solvent that is widely used in green tea leaf extraction is ethanol. Based on the results of the journal review, it can be concluded that the large amount of ethanol used in the maceration method of green tea leaf extract is based on ethanol's ability to penetrate cell walls and attract target compounds more quickly. Keywords: Leaf Extract, Green Tea, Maceration, Ethanol